2021
DOI: 10.1080/21645515.2021.1956228
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of booster BCG vaccination in preventing Covid-19 infection

Abstract: The evidence that BCG (bacille Calmette-Guerin) vaccine may increase the ability of the immune system to fight off pathogens other than tuberculosis has been studied in the past. This nonspecific immunity gained our interest, especially after initial reports of less cases in countries with universal BCG vaccination. In hopes of possible protective immunity, all staff of the Emirates International Hospital (United Arab Emirates) were offered a booster BCG vaccine in early March 2020. All the hospital staff were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…However, according to the results found in this case report, it is observed that in vulnerable of population in some regions in Mato Grosso do Sul State where the forms of advanced Tuberculosis occur there is the presence of strains of Mycobacterium Tuberculosis that are resistant to drugs as shown in Table 2. Nevertheless, higher rates of deaths can be expected in young individuals as evidenced by previous studies (Amirlak et al, 2021).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…However, according to the results found in this case report, it is observed that in vulnerable of population in some regions in Mato Grosso do Sul State where the forms of advanced Tuberculosis occur there is the presence of strains of Mycobacterium Tuberculosis that are resistant to drugs as shown in Table 2. Nevertheless, higher rates of deaths can be expected in young individuals as evidenced by previous studies (Amirlak et al, 2021).…”
Section: Discussionmentioning
confidence: 55%
“…Given the above, it is important to implement strict infection control interventions for all hospitalized vulnerable population, which consider the risk of viral transmission from other patients, visitors and health professionals (Amirlak et al, 2021). In this case, greater care should be given to patients at high risk such as the elderly and patients with comorbidities including Tuberculosis (Gao et al, 2020;Andrade Junior et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 , 23 Until such new vaccines are developed, booster BCG vaccination may be beneficial to prevent COVID-19 infection. 24 As of August 20, 2021, there are 296 vaccine candidates under development, of which 112 are in the clinical development stage. 25 The vaccine platforms include protein subunit, viral vector (replicating or non-replicating), DNA, RNA and inactivated virus.…”
Section: Discussionmentioning
confidence: 99%
“…A Phase III randomized clinical trial confirmed that recent vaccination with BCG protects the elderly against new respiratory infections ( 31 ). Also, booster BCG vaccination in high-risk healthcare workers was shown to prevent COVID-19 ( 32 ). Accordingly, in the mice model, BCG administration can protect from SARS-CoV-2 infection ( 33 ).…”
Section: Introductionmentioning
confidence: 99%